Analysis of Metacognitive Strategies Used in Intensive and Extensive Listening of English Department Students of UNP - Defitria, Laura; Solusia, Carbiriena (Journal of English Language Teaching, 2025)
This research aims to analyze metacognitive strategies used in intensive and extensive listening activities among fourth-year English Department students at Universitas Negeri Padang. The research method used was a quantitative approach with a descriptive design. The instrument used in this study was a closed-ended questionnaire adapted from the Metacognitive Awareness Listening Questionnaire (MALQ) by Vandergrift et al. (2006), which measures five key metacognitive strategies: planning and evaluation, directed attention, person knowledge, mental translation, and problem-solving. The sample was selected using cluster random sampling, with one class (K2-2021) chosen as the representative sample. The results of the study indicate that during intensive listening activities, the most commonly used strategy is “directed attention”, while the least commonly used strategy is “mental translation”. In extensive listening activities, the most commonly used strategy is “person knowledge”, while “planning and evaluation” is the least used. Furthermore, all five strategies were used at a high level in both listening contexts. These findings suggest that students are actively engaged in applying metacognitive strategies, both in classroom-based and autonomous listening practices. Based on these findings, it can be concluded that fourth-year English Department students at Universitas Negeri Padang demonstrate strong use of metacognitive strategies in their listening activities and are capable of using appropriate strategies effectively.